A multi-source book review system for reducing information overload and accommodating individual styles. Issue 3 (21st September 2015) - Kao, Gloria Yi-Ming; Peng, Chi-Chieh
Abstract : Purpose: – The purpose of this paper is to evaluate the performance of the multi-source book review system (MBRS). MBRS was designed to reduce information overload using the internet and to accommodate different learner preferences. Design/methodology/approach: – The authors experimentally compared MBRS with the Google search engine. MBRS first gathers reviews from online sources, such as bookstores and blogs. It reduces information overload through an advanced filtering and sorting algorithm and by providing a uniform user interface. MBRS accommodates different learning styles through various sort options and through adding video-mediated reviews. Findings: – Results indicate that, compared with Google, MBRS: reduces the information overload associated with searching for online book reviews; increases users finding satisfactory book reviews; and allows users to find reviews more quickly. In addition, more than half of the participants found video-mediated book reviews more appealing than traditional text-based reviews. Research limitations/implications: – Future studies might examine the effects of other recommendations or sorting methods to fit individual preferences in a more dynamic way. Practical implications: – This study assisted readers with a preference for visual information in locating reviews of personal interest in less time and with finding reviews more aligned with their individual learning preferences. Originality/value: – This study documents an innovative web site featuring video-mediated book reviews and other mechanisms to accommodate individual preferences. Search engine designers could integrate book reviews with different media types to reduce cognitive load allowing readers to focus attention on the reading task. Internet booksellers or library staff may use this as an effective means to enhance reading motivation.